Dysfunctional Factors of Environmental Law on Strategic Lawsuit Against Public Participation and Developing Remedial Strategies Through Reconstruction Criminal Law System Model in Indonesia - Hartiwiningsih, Hartiwiningsih; Gumbira, Seno Wibowo; Barkhuizen, Jaco (Faculty of Law, Universitas Padjadjaran, 2023)
The excessive criminalization of community and environmental enforcement activists has prolonged the problem of SLAPP (Strategic Lawsuits Against Public Participation) in Indonesia. This study explores the factors contributing to non-optimal protection for citizens and environmental law enforcement activists. It aims to develop an ideal model for formulating the criminal law system to address Indonesia's Strategic Lawsuit Against Public Participation (SLAPP). This study used a doctrinal juridical approach to analyze and identify the factors preventing environmental law from effectively providing legal protection to the community and activists advocating for a good, healthy, and safe environment or the occurrence of SLAPP. This research found that the new model should incorporate clear sentencing guidelines for law enforcement while addressing and reformulating conflicting legal instruments. The goal is to foster juridical harmonization, serving as a strategic approach to prevent SLAPP in the future.DOI: https://doi.org/10.22304/pjih.v10n3.a6